Sudan : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Sudan discusses that regime change has created a window of opportunity for fundamental reforms to address major macro imbalances and lay the groundwork for inclusive growth. The economy is shrinking, fiscal and external imbalances are large, inflation is high, the currency is overvalued, and competitiveness is weak. The humanitarian situation is dire with large numbers of internally displaced people and refugees. US sanctions on trade and financial flows were revoked in October 2017, but Sudan remains on the state sponsors of terrorism list, which effectively discourages external investment and blocks progress toward both heavily indebted poor countries debt relief and the clearance of large arrears to the IMF. In this context, staff engagement has intensified to render the necessary policy and technical assistance to help the authorities seize this once-in-a-generation opportunity for reforms. There is broad agreement between the authorities and the IMF staff about the key reform priorities, however, the authorities have yet to put together a fully coherent and viable plan that enjoys broad public support and can plausibly attract adequate donor financing.